2015
DOI: 10.1002/mnfr.201400630
|View full text |Cite
|
Sign up to set email alerts
|

Pea (Pisum sativum L.) seed albumin extracts show anti‐inflammatory effect in the DSS model of mouse colitis

Abstract: PSE and AF-PSE ameliorated DSS-induced damage to mice, their effects being due, at least partially, to the presence of active BBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 70 publications
5
62
0
3
Order By: Relevance
“…Unlike most IBD drugs, which must be administered systemically and are thus associated with serious side effects [67,68], GDNPs 2 are delivered orally, offering several advantages over other therapeutic routes. Importantly, oral administration supports our primary goal of delivering GDNPs 2 to the colon, which is the site of intestinal inflammation in ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most IBD drugs, which must be administered systemically and are thus associated with serious side effects [67,68], GDNPs 2 are delivered orally, offering several advantages over other therapeutic routes. Importantly, oral administration supports our primary goal of delivering GDNPs 2 to the colon, which is the site of intestinal inflammation in ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…In one research the effect of pissum sativum L on colitis which created by DSS (Dextrane Sodium Solphate) has been studied, and showed that pissum sativum L and its albumin part extract is BBI (Bowman-Birk Inhibitor) that care the harms of DSS. [17] …”
Section: Discussionmentioning
confidence: 99%
“…Por otra parte, proteí-nas de diferente estructura podrían digerirse y absorberse de modo diferente, lo que daría lugar a efectos diferentes sobre el hígado y, consecuentemente, influir sobre determinados parámetros o producir efectos nutricionales diferentes (Rubio y Seiquer, 2002). Resultados recientes de nuestro grupo (Utrilla et al, 2015) han mostrado un efecto antiinflamatorio de albúminas del guisante a nivel del colon en ratones, y otros datos no publicados sugieren un efecto directo de estas mismas proteínas sobre la absorción de glucosa en adipocitos. Es claro, por tanto, que la relación animal-alimento es más compleja de lo que se suponía hasta hace unos años, ya que no se limita a la mera incorporación de nutrientes, sino que implica una modificación, por parte de componentes del alimento, de funciones fisiológicas a veces bastante alejadas de las estrictamente nutricionales.…”
Section: Las Leguminosas Como Alimentos Funcionalesunclassified